Substitution
y = 2x - 12
y = -x + 3
-x + 3 = 2x - 12
+ x + x
-----------------------------
3 = 3x - 12
+ 12 + 12
-----------------------
15 = 3x
------ ------
3 3
x = 5
y = 2(5) - 12
y = 10 - 12
y = -2
The final answer is (5,-2).
Step-by-step explanation:
I am going to guest 25 mins
This is a problem involving the subtraction of two functions f(x) and g(x):
<span>if f(x)=3x-1 and g(x)=x+2, find (f-g)(x). In other words, find:
</span><span> f(x) = 3x-1
-{g(x) -(x+2)
-----------------
f(x) - g(x) = 3x - 1 - x - 2 = 2x - 3 (answer)</span>
Answer:
x= k/a-b
Step-by-step explanation:
Move all terms to the left side and set equal to zero as well as each factor.
Hope this helps.